2022
DOI: 10.1007/s11676-022-01565-3
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined effects of fertilization, ectomycorrhizal inoculation, and drought on container-grown Japanese larch seedlings

Abstract: Climate change can intensify drought in many regions of the world and lead to more frequent drought events or altered cycles of soil water status. Therefore, it is important to enhance the tolerance to drought and thus health, vigor, and success of transplantation seedlings used in the forestry by modifying fertilization and promoting mycorrhization. Here, we sowed seeds of Japanese larch (Larix kaempferi) in 0.2-L containers with 0.5 g (low fertilization; LF) or 2 g (high fertilization; HF) of slow-release fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…AMF are widely spread in natural and agricultural ecosystems, and their symbiotic relationship with most land plants provides important ecological services, e.g., increasing plant nutrition and tolerance to both abiotic and biotic stresses, including herbivorous pests [ 13 ]. The mycorrhizal status of plants is also a key factor leading to changes in plant physiology, e.g., nutrient dynamics and secondary metabolism [ 14 , 15 , 16 , 17 ], thus affecting the quality of plants as suitable hosts for insect pests [ 18 ]. AMF and UV-B may be involved in the modification of the emission of volatile organic compounds (VOCs), which are responsible for the communication of plants with the surrounding environment [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMF are widely spread in natural and agricultural ecosystems, and their symbiotic relationship with most land plants provides important ecological services, e.g., increasing plant nutrition and tolerance to both abiotic and biotic stresses, including herbivorous pests [ 13 ]. The mycorrhizal status of plants is also a key factor leading to changes in plant physiology, e.g., nutrient dynamics and secondary metabolism [ 14 , 15 , 16 , 17 ], thus affecting the quality of plants as suitable hosts for insect pests [ 18 ]. AMF and UV-B may be involved in the modification of the emission of volatile organic compounds (VOCs), which are responsible for the communication of plants with the surrounding environment [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the small container-grown seedlings do not grow taller than bareroot seedlings after planting [14,15]. Some studies have recently been conducted on methods to produce high-quality container-grown seedlings; however, knowledge regarding what characteristics contribute to the effective performance of container-grown Japanese larch seedlings after planting is still insufficient [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the important function of micronutrients in enhancing plant germination and growth, under abiotic stress conditions, polyamines (PAs) have a significant effect on enhancing tolerance to abiotic stresses . PAs are small organic polycations that are commonly prevalent in living organisms and are now regarded as a new class of growth substances that include spermidine, spermine, and their obligate precursor putrescine, which play a key role in regulating plant developmental and physiological processes .…”
Section: Introductionmentioning
confidence: 99%